Spatial price transmission in major East African horticultural markets : a thesis presented in partial fulfilment of the requirements for the degree of Master of AgriCommerce at Massey University, Manawatū, New Zealand - Lulah, Hermence Christopher (Massey University, 2015)
The objective of this study is to assess the integration of horticultural markets in East Africa. The analysis is conducted using monthly wholesale prices of fresh tomatoes and fresh onions. Four representative markets (two in Tanzania and two in Kenya) are selected for the analysis. These markets are analyzed in pairs using the bivariate Joe-Clayton copula (BB7). This copula involves two parameters, which control the degree of overall dependence of price shocks as well as the strength of dependence at the extremes of their joint distribution. The overall dependence is assessed by the Kendall’s tau, which is calculated from a number of concordant and discordant pairs of observations. Information about dependence at the lower and the higher ranks is obtained by measuring the upper and the lower tail dependence coefficients. These coefficients give the probability that a price shock in one market will be above (below) a high (a low) quantile if a price shock in another market is also above (below) a high (a low) quantile. When considered together, the overall strength of co-movement and co-movement at the extremes provide information about the degree of market integration. Empirical results of this study suggest that the investigated markets are generally not very well integrated. The overall dependence of price shocks between different pairs of markets varies from low to medium. The pattern of dependence of these price shocks also appears to be predominantly asymmetric.